Phase‐Change Heat Transfer: Supercapillary Architecture‐Activated Two‐Phase Boundary Layer Structures for Highly Stable and Efficient Flow Boiling Heat Transfer (Adv. Mater. 2/2020). Issue 2 (14th January 2020) - Li, Wenming; Wang, Zuankai; Yang, Fanghao; Alam, Tamanna; Jiang, Mengnan; Qu, Xiaopeng; Kong, Fengyu; Khan, Ahmed Shehab; Liu, Minjie; Alwazzan, Mohammad; Tong, Yan; Li, Chen
Abstract : The physical limit of flow boiling heat transfer is reported by Zuankai Wang, Chen Li, and co‐workers in article number 1905117 . Textured supercapillary structures are designed in a microfluidic device to fundamentally transform the conventional chaotic phase‐transition process into a desirable two‐phase boundary layer structure. Exceptional thermal performances are achieved.